Critical Analysis of the Commercial Potential of Plants for the Production of Recombinant Proteins - Schillberg, Stefan; Raven, Nicole; Spiegel, Holger; Rasche, Stefan; Buntru, Matthias (Frontiers in Plant Science, 2019)
Over the last three decades, the expression of recombinant proteins in plants and plant cells has been promoted as an alternative cost-effective production platform. However, the market is still dominated by prokaryotic and mammalian expression systems, the former offering high production capacity at a low cost, and the latter favored for the production of complex biopharmaceutical products. Although plant systems are now gaining widespread acceptance as a platform for the larger-scale production of recombinant proteins, there is still resistance to commercial uptake. This partly reflects the relatively low yields achieved in plants, as well as inconsistent product quality and difficulties with larger-scale downstream processing. Furthermore, there are only a few cases in which plants have demonstrated economic advantages compared to established and approved commercial processes, so industry is reluctant to switch to plant-based production. Nevertheless, some plant-derived proteins for research or cosmetic/pharmaceutical applications have reached the market, showing that plants can excel as a competitive production platform in some niche areas. Here we discuss the strengths of plant expression systems for specific applications, but mainly address the bottlenecks that must be overcome before plants can compete with conventional systems, enabling the future commercial utilization of plants for the production of valuable proteins.